2011
DOI: 10.1073/pnas.1017374108
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase JMJD2B coordinates H3K4/H3K9 methylation and promotes hormonally responsive breast carcinogenesis

Abstract: It is well-documented that the methylation of histone H3 lysine 4 (H3K4) and of H3K9 are mutually exclusive, an epigenetic phenomenon conserved from yeast to humans. How this opposed methylation modification is accomplished and coordinated in mammalian cells is poorly understood. Here we report that the H3K9 trimethyl demethylase JMJD2B is an integral component of the H3K4-specific methyltransferase, the mixed-lineage leukemia (MLL) 2 complex. We show that the JMJD2B/MLL2 complex is copurified with estrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
219
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(246 citation statements)
references
References 38 publications
16
219
4
Order By: Relevance
“…Wissmann and colleagues [41] have demonstrated that JMJD2C, which demethylases H3K9me3, and LSD1, which specifically demethylases H3K9 me2/me1, interact and cooperatively stimulate AR-dependent gene transcription. Recently it has been also reported, in ERa regulated transcription, a coordinated interaction among ERa and the H3K9me3 demethylase JMJD2B, and the H3K4 methyltransferase MLL2 complex has been recently reported [42]. Previous studies have underlined the importance of FAAH in male fertility [18,43], where this hydrolase controls the endogenous levels of AEA, and hence its signaling.…”
Section: Discussionmentioning
confidence: 93%
“…Wissmann and colleagues [41] have demonstrated that JMJD2C, which demethylases H3K9me3, and LSD1, which specifically demethylases H3K9 me2/me1, interact and cooperatively stimulate AR-dependent gene transcription. Recently it has been also reported, in ERa regulated transcription, a coordinated interaction among ERa and the H3K9me3 demethylase JMJD2B, and the H3K4 methyltransferase MLL2 complex has been recently reported [42]. Previous studies have underlined the importance of FAAH in male fertility [18,43], where this hydrolase controls the endogenous levels of AEA, and hence its signaling.…”
Section: Discussionmentioning
confidence: 93%
“…16,17 Therefore, we hypothesized that Kdm4b might also be involved in regulating MCE during 3T3-L1 preadipocyte differentiation. RNAi oligonucleotide of Kdm4b was transfected into 3T3-L1 preadipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that Kdm4b is required for estrogen receptor a (ERa)-regulated breast cancer progression and mammary epithelial cells (MECs) proliferation. [16][17][18] In the present study, Kdm4b was identified as a target gene of C/EBPb that functions as a co-factor of C/EBPb to demethylate H3K9me3 in the regulatory regions of C/EBPb-regulated cell cycle genes Cdc45l (cell division cycle 45 homolog), Mcm3 (mini-chromosome maintenance complex component 3), Gins1 (GINS complex subunit 1) and Cdc25c (cell division cycle 25 homolog c), thereby promoting their expression and MCE. This explains why C/EBPb is required for MCE during adipocyte differentiation.…”
mentioning
confidence: 99%
“…In principle, the exclusion of colocalized modifications could be explained by a methyltransferase that functions at H3K9 only in the absence of H3K4me3 (or vice versa). Indeed, several H3K9 methyltransferases are partially inhibited by H3K4me3 (16,17), and MLL2, a H3K4 methyltransferase, is similarly inhibited by H3K9me3 (18). Mutual exclusivity could additionally be achieved by demethylases that are selective for H3K9me3 in the presence of H3K4me3 (or vice versa).…”
mentioning
confidence: 99%